CHALLENGES IN GEOGRAPHY EDUCATION – A REVIEW OF RESEARCH PROBLEMS - Piotrowska, Iwona; Cichoń, Małgorzata; Abramowicz, Dawid; Sypniewski, Jakub (Quaestiones Geographicae, 2019)
Scientific research and student education aimed at preparing students to practice their profession under the conditions of civilization and technological changes play a special role in geography teaching. It is important to be aware of the impact of key competences which are necessary for every person to function in the modern world and are needed for self-fulfilment, personal development, social integration, flexible adaptation to any changes and which determine the success in adult life. Proper development of such skills contributes to the correct interpretation of natural and socio-economic phenomena and processes. The aim of the article is to present and discuss research work and teaching activities pursued by the Department of Geography Didactics and Ecological Education at the Faculty of Geographical and Geological Sciences of the Adam Mickiewicz University in Poznań, aimed at the use by students of various educational concepts and the resulting key competences necessary for their future work. Students also have the opportunity to develop soft competences, such as communication, courage of expression, self-esteem or responsibility for the group, to which employers have paid special attention in recent years. Therefore, comprehensive preparation of the student requires the implementation of specific educational concepts. The most important ones include bilingual education; CLIL, inquiry based science education (IBSE), project method, fieldwork, geographical educational trails, participation, as well as the use of geoinformation technologies, GIS and ICT.